2014
DOI: 10.4162/nrp.2014.8.3.304
|View full text |Cite
|
Sign up to set email alerts
|

Association between household food insecurity and nutritional outcomes among children in Northeastern of Peninsular Malaysia

Abstract: BACKGROUND/OBJECTIVESThe purpose of the study was to investigate the relationship between household food insecurity and nutritional status of children in low-income households. A cross sectional study involved a survey of households (n = 223) receiving the financial assistance.SUBJECTS/METHODSEligible mothers that fulfilled the inclusion criteria such as non-pregnant, non-lactating mothers, aged 18 to 55 years with their youngest children aged 2 to 12 years, were purposively selected. The Radimer/Cornell hunge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
51
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 28 publications
13
51
2
4
Order By: Relevance
“…The output of subsistence farming is mostly for local requirement with little or no surplus for trade [52], which ultimately impairs the household food security status. Household food insecurity is associated with poor linear growth, stunting [53]. …”
Section: Discussionmentioning
confidence: 99%
“…The output of subsistence farming is mostly for local requirement with little or no surplus for trade [52], which ultimately impairs the household food security status. Household food insecurity is associated with poor linear growth, stunting [53]. …”
Section: Discussionmentioning
confidence: 99%
“…The another earlier study among low income household in Kuala Lumpur found 27.7% households were food insecure [15]. The latest study in north-eastern Malaysia found 29.6% of the household were food insecure [16].…”
Section: Discussionmentioning
confidence: 99%
“…36 Rumah tangga dengan pendapatan tinggi dan tahan pangan memiliki alokasi pengeluaran yang cukup untuk pangan sehingga konsumsi pangan rumah tangga akan lebih beragam. 37,38 Tabel 3 juga menunjukkan bahwa nilai ratarata skor HDDS pada rumah tangga sangat tahan pangan cukup tinggi yaitu 8,9. Sementara pada rumah tangga tahan pangan dan rawan pangan sedang memiliki ratarata skor HDDS yang sama masing-masing sebesar 7,8 dan 7,6.…”
Section: Hasil Dan Pembahasanunclassified